(untitled) - Porter, David (London, 2008)
This workbook contains exercises to help teach and practise the vocabulary students need for academic purposes. Written for students at upper-intermediate level and above, this workbook aims to help those who need to learn basic non-technical vocabulary so that they can study any subject at college or university. The material uses exercises, gap-fills and puzzles to test grammar, comprehension and spelling
Keywords: Tiếng Anh,Vocabulary,English language,Từ vựng; Học và giảng dạy,Nói tiếng nước ngoài,Study and teaching (Higher),Foreign speakers,Câu hỏi, bài tập,vv